SCREENING OF RESTRICTION ENZYMES FOR THE DEVELOPMENT OF RESTRICTION FRAGMENT-BASED, GENOMIC BIOMARKER OF ALCALIGENES JAVAENSIS - Ethica, Stalis Norma; Semiarti, Endang; Raharjo, Tri Joko; Oedjijono, Oedjijono; Sulistyaningtyas, Ayu Rahmawati; Darmawati, Sri (LIFE: International Journal of Health and Life-Sciences, 2019)
Alcaligenes javaensis is a food-borne, Gram-negative bacterium, which has the closest relationship with Alcaligenes faecalis commonly causing contamination of clinical equipment and infection on humans. Hence, the development of a biomarker for members of genus Alcaligenes including A.javaensis is needed for early detection of this bacterium. This research aimed to screen the performance of 5 restriction enzymes consisting of EcoRV, Hind III, NotI, SalI, and BgIII as singles and in combinations to produce specific pattern of restricted, genomic DNA fragments of A.javaensis. Total DNA was first extracted from subcultured A.javaensis cells using DNA isolation kit and the obtained DNA isolate was then subjected to enzyme restrictions in vitro. Later, the restricted DNA fragments were evaluated using agarose gel electrophoresis method. Results showed that only the EcoRV-BgIII-HindIII combination within a restriction process of 18 h could produce smaller-sized DNA bands, while those from other combinations (5 enzymes as singles and their 2-combinations) could not do so. As conclucion, the combination of EcoRV-BgIII-HindIII is the most potential among the evaluated endonucleases to be used as a genomic biomarker for A.javaensis.